2019
DOI: 10.1039/c8sc03510e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of near-infrared fluorescent Pdots for tumor targeting: aggregation-induced emissionversusanti-aggregation-caused quenching

Abstract: This article presents the first work to fundamentally study the effect of steric hindrance in Pdot systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 70 publications
2
45
0
Order By: Relevance
“…As a result, Pdots have recently found application in single‐particle tracking in cells, [35] lateral flow or blot‐style assays, [36, 37] and immunolabeling of cancer cells [38] . Despite this growing interest, Pdots with NIR emission remain rare [39–41] …”
Section: Introductionmentioning
confidence: 99%
“…As a result, Pdots have recently found application in single‐particle tracking in cells, [35] lateral flow or blot‐style assays, [36, 37] and immunolabeling of cancer cells [38] . Despite this growing interest, Pdots with NIR emission remain rare [39–41] …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, FI, as a highly sensitive and noninvasive technique, is also used as a powerful tool for clinical diagnosis. [ 46–48 ] Compared to conventional aggregation‐caused quenching (ACQ) luminogens, aggregation‐induced emission (AIE) luminogens are a kind of fluorogen that have weakly fluorescence when molecules are uniformly dispersed in solution but have strong fluorescence when aggregating. [ 49–54 ] For instance, Tang et al reported a novel small molecule dual‐modal MRI CA, consisted of a hydrophobic tetraphenylethylene (TPE) fluorophore and two hydrophilic gadolinium (Gd) diethylenetriaminepentaacetic acid moieties, for both magnetic and FI.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Additionally, optical interferences (e.g., autofluorescence) should be minimized as it may cause high background signals and hence limit the detection sensitivity. [ 6 ] Fluorescent nanoparticles (FNPs) based on inorganic compounds, [ 7 ] semiconductor quantum dots (Qdots), [ 8 ] semiconducting polymer dots (Pdots), [ 9 ] organic dyes, [ 10 ] and carbon dots (CDs) [ 11 ] have been generated and extensively investigated. However, it has been shown that most of the inorganic fluorescent materials have certain inherent limitations including high biological toxicity, non‐degradability, poor biocompatibility, or high cost.…”
Section: Introductionmentioning
confidence: 99%